Helicobacter pylori Infection Elicits Type I Interferon Response in Human Monocytes via Toll-Like Receptor 8 Signaling - Chalystha Yie Qin Lee; Yee Teng Chan; Yi Ying Cheok; Grace Min Yi Tan; Ting Fang Tang; Heng Choon Cheong; Jamuna Vadivelu; Suhailah Abdullah; Chung Yeng Looi; Won Fen Wong (Journal of Immunology Research)
Helicobacter pylori colonization and persistence could precede gastric adenocarcinoma. Elucidating immune recognition strategies of H. pylori is therefore imperative to curb chronic persistence in the human host. Toll-like receptor 7 (TLR7) and TLR8 are widely known as viral single-stranded RNA (ssRNA) sensors yet less studied in the bacteria context. Here, we investigated the involvement of these receptors in the immunity to H. pylori. Human THP-1 monocytic cells were infected with H. pylori, and the expression levels of human Toll-like receptors (TLRs) were examined. The roles of TLR7 and TLR8 in response to H. pylori infection were further investigated using receptor antagonists. Among all TLR transcripts examined, TLR8 exhibited the most prominent upregulation, followed by TLR7 in the THP-1 cells infected with H. pylori J99 or SS1 strains. H. pylori infection-mediated IFN-α and IFN-β transactivation was significantly abrogated by the TLR7/8 (but not TLR7) antagonist. Additionally, TLR7/8 antagonist treatment reduced H. pylori infection-mediated phosphorylation of interferon regulatory factor 7 (IRF7). Our study suggests a novel role of TLR8 signaling in host immunity against H. pylori through sensing live bacteria to elicit the production of type I interferon.